A study on factors that affect the business success in Malaysia - a case study in Selangor / Rohani Abdul Rahman and Mohammad Syafik Mohd Salim - Abdul Rahman, Rohani; Mohd Salim, Mohammad Syafik (2014)
The purpose of this study was to determine the significance factors that influence business success in Malaysia. The variables consists of basic knowledge of business, leadership skills and managerial skills which are stated as independent variables for this study. The respondents consists of 110 entrepreneurs around Selangor. The finding showed that basic knowledge in business, leadership skills and managerial skills have influence on business success in Malaysia. Two variables show positive relationship towards the unemployment among graduates which are basic knowledge of business and leadership. Managerial skill show negative relationship in this research finding. This study refers to primary data and also secondary data for supporting the sampling technique. Meanwhile, the researchers use questionnaires as the method to collect all the data from sample respondents in accomplishing the research objectives. The data for this study had been analysed using multiple statistical procedures; mean point value, standard deviation, and correlation analysis. The result of the study presented in this research agrees that basic knowledge of business and leadership skills influenced business success in Malaysia. This study can be seen as a foreword to a more detailed study to be carried by future research on the issue of Business success in Malaysia.